Attention as a Process of Selection, Perception as a Process of Representation, and Phenomenal Experience as the Resulting Process of Perception Being Modulated by a Dedicated Consciousness Mechanism - Bachmann, Talis (Frontiers in Psychology, 2011)
Equivalence of attention and consciousness is disputed and necessity of attentional effects for conscious experience has become questioned. However, the conceptual landscape and interpretations of empirical evidence as related to this issue have remained controversial. Here I present some conceptual distinctions and research strategies potentially useful for moving forward. Specifically, we should differentiate between processes and the results of the processes, move the emphasis from studying the effects of attention on the modality-specific and feature-specific perception to studying attentional effects on panmodal universal attributes of whatever conscious experience there is, and acknowledge that there is a specialized autonomous mechanism for leading to conscious experience of the preconsciously represented contents apart from the mechanisms of perception, attention, memory and cognitive control.